PENGARUH MOTIVASI INSTRINSIK DAN MOTIVASI EKSTRINSIK TERHADAP PRODUKTIVITAS KERJA KARYAWAN CV. MAJU JAYA - kharisma arwandita kurniawan arwandita kurniawan (JURNAL EKOBIS DEWANTARA, 2018)
This study aims to determine motivation motivation and extrinsic motivation on work productivity of CV employees. Fast forward. Based on the results of the research conducted on the variables of intrinsic motivation and extrinsic motivation that are significant to the work productivity of employees both partially and simultaneously.